When competences become occupational opportunities: how informal and non-formal learning can be recognised and used in Europe - Gaylor, Claudia; Schöpf, Nicolas; Severing, Eckart; Reglin, Thomas (Gütersloh, 2016)
"This summary evaluates the opportunities and challenges for recognising and validating informal learning in Europe. Best practice examples are shown on the basis of core elements and quality criteria in a cross-country comparison of Austria, Denmark, France, Finland, Germany, UK, The Netherlands and Norway."